Development policy and foreign affairs - Peter Hermes (Intereconomics, 1974)
According to the purist view development policy amounts to the pursuit of its main objective as against those of foreign, economic and agricultural policy, i. e., to ensure that donor interests should give way as far as possible to this target. It is however self-evident that “practical development policy”, being only one part of our whole policy, cannot play such a decisive role. Therefore foreign policy and development policy do not clash if both are properly conceived.
Keywords: 330; Germany